Coverage of birth registration in municipal corporation area of Ahmedabad, India - Jain, Kamlesh G.; Chandwani, Haresh R.; V., Bala D.; Trivedi, Kartik N. (International Journal Of Community Medicine And Public Health, 2017)
Background: It is a recognized child right to acquire a name and a nationality, and birth registration may be necessary to allow access to services. Birth registration is not only a matter of human rights but it also serves as an important instrument for planning about health, education and overall development. This study examines level of registration of birth in the Municipal Corporation area of Ahmedabad and to study the perception of people about birth registration system. Methods: Observational descriptive study was carried out in urban area of Ahmedabad Municipal Corporation which consists of six zones. One ward from each zone was chosen randomly for the study. The sample size was determined as per the total births registered in that particular year, which came out to be 940. The required sample size was stratified according to different zones depending on the births occurring in that particular zone. To know the perception of people about birth registration, house to house visit was carried out in the defined area. Only those parents whose children were ≤3 years were interviewed. Data collected was analyzed using Epi-Info software. Results: Out of 940 children, 889 (94.57%) were registered and mean age of child was 1.906±092 years. Number of registrations increased with the educational status of the parents and birth order. Only 838 (94.3%) had applied for the registration of their child within stipulated time (<21 days) and mean time for getting the certificate was 1.46 days. The main reason for the delay was absenteeism of staff. The main source of information was hospital. The main use of registration was stated as admission in schools and colleges by 746 (83.9%). Conclusions: The present study showed high levels of birth registration which were related to the awareness among the urban population regarding birth registration. Therefore, the efforts should be continued to make the community aware and sensitize regarding the importance and usefulness of birth certificate.